2003
DOI: 10.1192/bjp.182.4.312
|View full text |Cite
|
Sign up to set email alerts
|

Exposure therapy and sertraline in social phobia: 1-year follow-up of a randomised controlled trial

Abstract: Exposure therapy alone yielded a further improvement during follow-up, whereas exposure therapy combined with sertraline and sertraline alone showed a tendency towards deterioration after the completion of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(85 citation statements)
references
References 27 publications
4
80
0
1
Order By: Relevance
“…Exposure patients only reached the degree of improvement that the sertraline patients already had during the acute study. Improvement was also shown in the placebo group, so that the effects were probably due to spontaneous remission (Bandelow 2004; Bandelow and Haug 2004;Haug et al 2003).…”
Section: )(E)mentioning
confidence: 99%
“…Exposure patients only reached the degree of improvement that the sertraline patients already had during the acute study. Improvement was also shown in the placebo group, so that the effects were probably due to spontaneous remission (Bandelow 2004; Bandelow and Haug 2004;Haug et al 2003).…”
Section: )(E)mentioning
confidence: 99%
“…What was not discussed is the obvious inappropriateness of sertraline as first-line treatment due to its very low response and remission rates that are very unlikely to be better than those of placebo. Further, once sertraline is introduced, one is left with an iatrogenic comorbidity that is likely to have a negative effect on cognitive behavioral therapy, as was found to be the case in a placebo-controlled study [77]. Why not treating those patients with clonazepam only from the beginning?…”
Section: Ad In Anxiety Disordersmentioning
confidence: 99%
“…Unfortunately, very little research has been conducted on the long-term efficacy of combination treatment. However, one study by Haug et al [103], a 1-year follow-up study from the trial by Blomhoff et al [100], found that exposure alone continued to improve during the follow-up period but sertraline and sertraline plus exposure showed deterioration during the follow-up period. The authors concluded that perhaps one reason for this finding is that: 'exposure techniques applied in situations with low levels of anxiety achieved by medication may have less impact than exposure therapy applied in situations with a higher level of anxiety and may lead to a higher degree of relapse after end of treatment'.…”
Section: Combined Pharmacotherapy and Psychotherapy: Are Two Better Thamentioning
confidence: 99%
“…One naturalistic treatment study showed that pre-existing antidepressant use neither enhanced nor detracted from the effectiveness of group CBT for SAD [126]. By contrast, a 1-year follow-up study of a randomized controlled trial showed that patients who had received combination treatment of sertraline and exposure deteriorated during the follow-up period, while those who had received exposure therapy alone experienced further improvement during the follow-up period [103]. Additional research needs to be conducted in this area to determine what long-term impact medication in general may have on exposure therapy for SAD.…”
Section: Ssris/snris and Exposurementioning
confidence: 99%